Mechanical Properties Of The Friction Stir Welded Dissimilar Aluminium Alloy Joints - Varma, Ramaraju Ramgopal; Abdullah, Ibrahim; Muhamad Arifpin, Mansor (Institute of Research and Journals (IRAJ), 2014)
The present investigation aims in assessment of the mechanical properties of friction stir welded dissimilar metal alloy joints. The optimized process parameters have been predicted for obtaining the strength of the joints in comparable to the base metal. Aluminum 5083 and aluminum 6061 sheets of 5mm thick have been considered for fabricating the dissimilar joints due to their range of usage in most of the engineering applications. Dissimilar FS welded joints were fabricated by varying the process parameters like rotational speed, traverse speed and axial force fixing the Al 5083 on the advancing side and Al 6061 on the retreating side. Two levels of these parameters have been chosen at 1000 rpm and 1600 rpm, 40mm/min and 160 mm/min and 2.5kN and 3.5kN for rotational speed, traverse speed and axial force respectively. Taguchi technique was used to optimize the process parameters by selecting an L-8 orthogonal array consisting of 8 experimental runs. The mechanical properties like the yield strength, elongation, tensile strength and micro hardness of these joints fabricated has been evaluated at all these process parameters.